The place of retroviruses in perinatal pathology (review of literature) - A. V. Kolobov (Журнал инфектологии)
Review deals with HIV infection in pregnant women and mechanisms of vertical transmission of virus from mother to fetus. The role of placenta as defensive barrier is evaluated, as well as pathological changes in villous chorion, which can lead to disturbance of its function.